An ammonia supplying system using ammonium salt to reduce the NOx emissions of a 1.1 MW marine engine. Issue 1 (2nd January 2023) - Woo, Sang-Hee; Raza, Hassan; Kang, Won-Mo; Choe, Sang Bom; Im, Myeong Hwan; Lim, Kyung Sun; Nam, Jeong Gil; Kim, Hongsuk
Abstract : A solid-SCR (selective catalytic reduction) system using ammonium carbamate (AC) was designed to improve NOx emission reduction efficiency and compensate for the shortcoming of the UWS (urea water solution)-SCR system applied to marine diesel engines. The solid-SCR system was installed on the exhaust line of a 1.1 MW engine for electric power generation in a ship, and its performance of emissions reduction was compared with the existing UWS-SCR system. The NOx emitted from the engine was 9.2 g/kWh, and it is reduced to 1.94 g/kWh when using the UWS-SCR system. Using the solid-SCR system significantly lowered NOx emissions to 0.3 g/kWh, which was 15% of the UWS-SCR system. In addition, the solid-SCR system showed fewer ammonia slip characteristics than the UWS-SCR system. In the solid-SCR system, gaseous ammonia was directly supplied in the exhaust line, and it mixed well with the exhaust gas and reacted well with NOx in the SCR catalyst. An endurance test of the solid-SCR system was conducted for 210 h during actual ship operation. The NOx reducing efficiency was maintained at higher than 90% for 210 h. The AC consumption rate was 1.7–4.3 kg/h for the endurance test.